Differential circulating and visceral fat microRNA expression of non-obese and obese subjects. Issue 3 (March 2020) - Kim, Nan Hee; Ahn, Jiyun; Choi, Yong Min; Son, Hyo Jung; Choi, Won Hee; Cho, Hyun Joo; Yu, Ji Hee; Seo, Ji A; Jang, Young Jin; Jung, Chang Hwa; Ha, Tae Youl
Summary: Background & aims: Altered microRNA (miRNA) expression is associated with the pathophysiology of obesity; however, little is known about the miRNAs commonly dysregulated in the blood and visceral fat tissue of obese patients. This study compared the circulating and visceral fat miRNA expression in subjects with and without obesity. Methods: For the circulating miRNA study, 20 healthy control and 30 obese subjects were recruited. For the tissue miRNA expression study, omental fat tissue was collected in ten female subjects each in the control and obese groups. MiRNA expression was measured by TaqMan low-density arrays. Metabolic risk factors were measured. Target genes for selected miRNAs were analyzed using informatics tools and a functional network map was constructed. Results: 11 miRNAs were down-regulated (miR-133a, -139-5p, -15b, -26a, -301, -30b, -30c, -374, -451, -570, and -636), and one was up-regulated (miR-155) in both depots in obese subjects. These miRNAs had significant associations with BMI, waist circumference, and fat mass. Among them, miR-15b, miR-26a, miR-301, miR-30b, and miR-30c had more predicted obesity-related target genes than other miRNAs. In particular, miR-15b had numerous target genes associated with adipogenesis, mammalian target of rapamycin (mTOR) signaling, diabetes and insulin resistance, and mitochondrial function. Conclusions: It is suggested that the miRNA alteration in the serum and visceral fat has pathophysiological implications for obesity. Our study identified dysregulated miRNAs that may be novel therapeutic targets to combat obesity.